Corotating interaction region (CIR) induced magnetic storms during solar minimum and their effects on low-latitude geomagnetic field and ionosphere - Veenadhari, B.; Kumar, Sandeep; Tulasiram, S.; Singh, Rajesh; Alex, S. (My University, 2012)
The corotating interaction region (CIR) induced magnetic storms which occurred during solar minimum are investigated to study their effects on equatorial and low-latitude ionosphere and geomagnetic field at Indian sector. This work was a part of Indian CAWSES campaign for the period of March – April 2006. The penetration electric fields play a crucial role in modifying equatorial electric fields during severe magnetic storms and these effects are not studied in detail for moderate magnetic storm originated by CIRs. The present paper investigates the effects of CIR related moderate storms and found that during the moderate magnetic storms, the short lived (duration of 2 - 3 h) penetration of high latitude electric fields to equatorial ionosphere exists during local morning and noon hours during main phase as inferred from changes in EEJ with the response to interplanetary electric field. The variations of EEJ are linearly correlated with the sudden changes in interplanetary electric field (IEFY) around morning to noon hours, which confirms existence of the penetration of electric fields.
Keywords: Geomagnetic storm; Corotating interaction region (CIR); Interplanetary electric field; Equatorial electrojet (EEJ) strength; Penetration electric field; F-region critical frequency